STRATEGI TRANFORMASI MEDIA LOKAL RIAU TELEVISI DALAM PEMANFAATAN PLATFORM DIGITAL - Yogi Sasta Rahardja; Yasir; Suyanto (KAGANGA KOMUNIKA: Journal of Communication Science, 2026)
This research discusses Riau Televisi's local media transformation strategy in utilizing digital platforms as an effort to maintain its existence amidst developments in communication technology. Riau Televisi, which previously focused on conventional television broadcasts, has begun developing digital platforms such as YouTube, Instagram, Facebook, TikTok and online news portals as a means of distributing information. This research aims to find out how Riau Televisi plans, implements and evaluates digital transformation strategies in utilizing digital platforms. The research method used is a qualitative method with a descriptive approach. The data obtained was then analyzed using media convergence theory and mediamorphosis theory to understand the transformation process that occurred. The research results show that Riau Televisi's digital transformation was carried out through several stages, namely determining priority platforms, adjusting content and audience segmentation, producing and distributing multi-platform content, optimizing audience interaction, and evaluating and monitoring digital performance. Then digital platforms also make it easy for audiences to access information quickly and practically. Digital platforms function as initial media for disseminating information, while television broadcasts remain a source of more complete and in-depth information. This shows that digital media and television have a complementary relationship. Apart from that, audience interaction via social media is also an important indicator in assessing the success of published content. Content performance data is used as a basis for determining subsequent content production and distribution strategies.   Keywords: Digital Transformation, Local Media, Riau Television, Digital Platform